2014
DOI: 10.1007/s13365-014-0252-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in PINCH levels in the CSF of HIV+ individuals correlate with hpTau and CD4 count

Abstract: Several studies report associations between the PINCH (particularly interesting new cysteine histidine-rich) protein and HIV-associated CNS disease. PINCH is detected in the CSF of HIV patients and changes in levels during disease may be indicative of changes in disease status over time. PINCH binds hyperphosphorylated Tau (hpTau) in the brain and CSF, but little is known about the relevance of these interactions to HIV CNS disease. In this study, PINCH and hpTau levels were assessed in three separate CSF samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Further studies revealed that PINCH and hpTau bind one another, and that this interaction may be important for the regulation of hpTau’s interaction with heat shock machinery [40]. In other studies, changes in the levels of PINCH and hpTau in CSF of HIV patients were shown to correlate directly with one another [1]. Taken together, results from this study and others support an important role for PINCH in tau phosphorylation.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Further studies revealed that PINCH and hpTau bind one another, and that this interaction may be important for the regulation of hpTau’s interaction with heat shock machinery [40]. In other studies, changes in the levels of PINCH and hpTau in CSF of HIV patients were shown to correlate directly with one another [1]. Taken together, results from this study and others support an important role for PINCH in tau phosphorylation.…”
Section: Discussionsupporting
confidence: 70%
“…Recently identified as a binding partner of hpTau, the PINCH protein [1,27,40,44] is involved in protein recruitment, protein complex assembly and shuttling throughout the cell (for review, see [29]). During brain development, PINCH is expressed at high levels and functions in cytoskeletal organization and communication between the cell and the extracellular matrix [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These surrogate markers are believed to reflect the amount of abnormal Tau present in the brain and CSF. In particular, the LIM-domain only protein PINCH has gained some recent attention (Adiga et al, 2014; Ozdemir et al, 2013), but it remains to be seen if this protein truly correlates with the levels of abnormal Tau in the brain and CSF, and/or if it can be used to predict cumulative damage after repetitive TBI.…”
Section: Perspectives Future Directions and Conclusionmentioning
confidence: 99%
“…53 Unexpectedly, the amount of PINCH in CSF did not display a positive correlation with the CSF virus burden, but was related to the immune responses in patients. 54 Further studies are required to reveal the exact role and significance of PINCH in central nervous system diseases induced by HIV infection.…”
Section: Pinch and Binding Partnersmentioning
confidence: 99%